Reference management in written narrative production by Spanish-Italian bilingual children - Leonetti Escandell, Victoria (Frontiers in Communication, 2024)
This paper is an investigation of reference production in 84 Italian-Spanish bilingual children aged 8 to 12. The study explores whether such reference production is influenced by either the type of referential expression involved or language dominance by analyzing how these children manage reference. The children's relative proficiency in the two languages (and thus their language dominance) was assessed through a cloze-test, and their narrative production was evaluated using a retelling task. Results indicated a preference for null pronouns to refer to subjects and full referential expressions for objects, with Italian showing a higher occurrence of full referential expressions. Dominance in either language did not significantly impact reference production. This suggests that bilingual children can distinguish between language-specific patterns, a behavior consistent with adult monolingual groups. These results contribute to our understanding of bilingual reference management and shed light on the role played by language and language dominance.